Studies on entry events during calicivirus replication - Shivanna, Vinay (Kansas State University, 2014)
Caliciviruses are important pathogens of humans and animals. Noroviruses are major causes of foodborne gastroenteritis cases, but their research is hindered due to the inability to grow human noroviruses in cell culture. Detailed studies on entry events of caliciviruses are lacking and may be crucial for development of cell culture models. We examined the entry events of caliciviruses using porcine enteric calicivirus (PEC), feline calicivirus (FCV) and murine norovirus-1 (MNV-1). PEC replication in LLC-PK cells requires bile acid in the medium, but the mechanism is not well understood. Our studies showed that bile acids are required in the early stage of virus replication, and while internalization of PEC is not dependent of them, they are required for endosomal escape and successful replication. Further examination on virus entry, we demonstrated that endosomal acidification and cathepsin L activity are essential in the replication of PEC, FCV and MNV-1. The results showed that inhibition of endosomal acidification or cathepsin L activity led to retention of viruses in the endosomes. Also we demonstrated that recombinant cathepsin L cleaved structural protein of PEC, FCV or MNV-1, which suggests that the enzyme may facilitate uncoating viruses in endosomes. In addition to bile acids, we found that a cold shock treatment during virus entry supported PEC replication by facilitating the endosomal escape. While PEC alone did not induce ceramide formation, bile acids or cold shock treatment induce ceramide formation on endosomes through activation acid sphingomyelinase (ASM), and this event was crucial for virus replication because inhibition of ASM blocked ceramide formation and significantly reduced PEC replication. Incubation of FCV or MNV-1 with cells led to ceramide formation during virus entry, and inhibition of ASM also significantly reduced their replication. Inhibition of ASM led to endosomal retention of PEC, FCV or MNV-1 during virus entry, which may be the reason for the reduction of viral replication. These studies revealed the important and common events during calicivirus entry for successful replication, including virus endosomal escape, cathepsin L activity and ASM/ceramide formation. This detailed information may provide clues for understanding the replication of fastidious caliciviruses and for potential therapeutic targets.
Keywords: Calicivirus; Bile acid; Endosomal escape; Cathepsin; Endosomal acidification; Acid sphingomyelinase; Virology (0720)